2016
DOI: 10.4997/jrcpe.2016.413
|View full text |Cite
|
Sign up to set email alerts
|

Current Clinical Controversies in the Management of Sepsis

Abstract: Sepsis remains a challenging clinical problem requiring prompt diagnosis and optimal clinical management if the continuing high mortality is to be contained. In this brief review I consider four specific questions that are the subject of ongoing controversy. First, whether the new 'Sepsis-3' definitions will be helpful, in particular in improving diagnosis, or whether the rapid move towards precision medicine will make the definition redundant. Second, should we routinely use combinations of antibiotics for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…34 PCT values help in deciding about the need for antibiotics and duration of antibiotic therapy. 35 It was also found that use of PCT helps in reduction of antibiotic prescription between 11% and 74%, and reduction of days of antibiotic therapy by between 13% and 55%. 36 In patients admitted to ICU use of PCT-based algorithm resulted in the reduction of antibiotic therapy for the initial infection by 2 days and the total duration of antibiotic therapy by 4 days.…”
Section: Macrophage Migration Inhibitory Factormentioning
confidence: 96%
“…34 PCT values help in deciding about the need for antibiotics and duration of antibiotic therapy. 35 It was also found that use of PCT helps in reduction of antibiotic prescription between 11% and 74%, and reduction of days of antibiotic therapy by between 13% and 55%. 36 In patients admitted to ICU use of PCT-based algorithm resulted in the reduction of antibiotic therapy for the initial infection by 2 days and the total duration of antibiotic therapy by 4 days.…”
Section: Macrophage Migration Inhibitory Factormentioning
confidence: 96%